Assessment of successful treatment rate of health care facilities by rural dwellers in Owo region, Nigeria: a challenge for rural development - J.A.B., Olujimi; K. , Rotowa; D. , Samuel (2008)

(untitled)
One of the important parameters that distinguish the developed countries from the less developed ones is the people’s health status, which in the latter is still very low. The less developed countries, of which Nigeria is one, are characterised by high infant mortality rate, high prevalence of communicable diseases as well as high level of illiteracy and ignorance (Egunjobi, 1996). The human, economic, and societal costs of ill health are immense. Millions of people die prematurely from diseases that are preventable or curable (Carr, 2004). The effect of this is much felt among the rural dwellers, who are living in areas that are provided with very few and poor health care facilities. This paper assesses the successful treatment rate of health facilities in Owo region, Nigeria by rural dwellers with a view to promoting the patronage of these facilities in order to improve their health conditions as means of boosting their economic and welfare status. Owo region habours tertiary, secondary, and primary health care facilities and the region comprises of 2 urban settlements and 193 rural settlements. This provides a study area that mirrors a typical Nigerian situation. Three different sets of questionnaires were designed and used for the collection of primary data for the study. However, secondary data relevant to the study were sought. The primary data were subjected to both qualitative and quantitative analysis. Furthermore, some of the information were presented in form of tables, graphs, and others were subjected to statistical test; a paired-sample t-test was used in testing the hypothesis which was used in comparing the treatment success rate between the government-owned health facilities and private-owned health facilities in the region. Our findings revealed that the rural dwellers patronised both urban- based and rural -based health facilities. Both the government, and private-owned health care facilities located in the rural areas render very low and poor health care services. The success treatment rate at the government-owned health care facilities is significantly different from that of the private-owned facilities; yet the rural dwellers patronised the private-owned health care facilities, which are mostly dominated by quacks. In view of the expectations from different health programmes such as roll back malaria; fight against the scourge of HIV/AIDS; eradication of Tuberculosis, etc, the paper calls for a deserved attentions to be given to the rural areas.